Focal nodular hyperplasia in a 14-year-old child: A case report - Farzan Vahedifard; Masoud Mortezazadeh; Abbas Mofidi; Mehdi Kashani; Alireza Sharifi Rayeni (Babol University of Medical Sciences, 2021)
Background: Focal nodular hyperplasia (FNH) is a benign rare liver neoplasm in children and includes only 2% of all pediatric liver tumors. Here we reported the case of a 14-year-old girl with vague flank pain who was managed conservatively. Case Presentation: Our case is a 14-year-old child (female), with a 5 cm diameter lesion in the right lobe of the liver in CT scan, and histologic findings compatible with FNH. A solid mass lobulated contour, intense enhancement with a hypodense central area, possibly indicative of central scar, was seen. Despite her mild flank pain we did not insist on surgical resection and managed her conservatively. Her pain resolved 2 weeks later and an imaging follow-up with ultrasound 6 months later showed no increase in size or numbers. Conclusion: FNH is an uncommon mass lesion in children. Our patient had mild symptomatic severity, and several guidelines recommend surgical treatment in this condition, but our team performed conservative and medical treatment for her and got the desired result. Therefore, the combination of these factors raises the importance of introducing the case. According to FNH's nature, stability, complications, and evaluation of pain are essential to avoid unnecessary surgeries.